Interactions effects of nano-microplastics and heavy metals in hybrid snakehead (Channa maculata ♀ × Channa argus ♂). Issue 124 (May 2022) - Wang, Shaodan; Xie, Shaolin; Zhang, Chaonan; Pan, Zhengkun; Sun, Di; Zhou, Aiguo; Xu, Guohuan; Zou, Jixing
Abstract: The interaction between microplastics and contaminants has potentially generated new undefined risks on animals and ecosystems, and nano-microplastics are considered to be more harmful than microplastics. This experiment investigated the interactions and effects of nano-microplastics with heavy metals cadmium in hybrid snakehead. Different concentrations of nano-microplastics 80 nm (50 μg/L and 500 μg/L) and Cd (50 μg/L) were used for exposure, and four sampling points were set for 24 h, 48 h, 96 h and clear-48 h. Results indicated that the morphology of gill was altered under the influence of nano-microplastics and cadmium, and the damage was aggravated with time. Nano-microplastics and Cd can cause oxidative damage to fish liver partly by effect the activities of antioxidant enzyme, and significantly suppressed the expressions of genes related to the inflammation ( IL-1β and TNF-α ) and as well as significantly up-regulated the expression of genes HSP70 and SOD . Additionally, the mRNA levels of MT gene can be speculated that the heavy metal cadmium may accumulated in the body over time. And the concentration of heavy metals will also affect their accumulation in the body. Our study elucidated the nano-microplastics and Cd will increase the impact on environmental and organisms that the nano-microplastics contribute to the bioaccumulation of metals, which served as a new support for study the interaction between environmental contaminants. Graphical abstract: Image 1 Highlights: The effects of Cd and nano-microplastics were investigated in Hybrid snakehead. Exposure to Cd or nano-microplastics alone alters biochemical and immunological parameters. The combination of nano-microplastics and Cd exerts both antagonism and synergistic toxicity. The environmental pollution risks of nano-microplastics and cadmium should be combined and analyzed.